2014
DOI: 10.1159/000368082
|View full text |Cite
|
Sign up to set email alerts
|

Association between Single Nucleotide Polymorphisms in the OPRM1 Gene and Intraoperative Remifentanil Consumption in Northern Chinese Women

Abstract: SNP rs558025 in the OPRM1 gene was associated with intraoperative remifentanil consumption during gynecological hysteroscopic surgery in our subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
12
1
Order By: Relevance
“…Chau et al, 16 found that patients with AA genotype required less postoperative morphine dose than patients with genotype AG or AA. Also, Liu et al, 6 found that patients carrying one or 2 copies of the minor allele (G allele) required significantly more intraoperative remifentanil than in patients without the minor allele ( p =0.001). We performed our study on Jordanian patients (Arab ethnic group) and our findings coincide with Liu et al, 6 where the remifentanil consumed in the intra-operative time to maintain a SBP between 90-100 mm Hg was higher in AG gene compared with AA gene.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Chau et al, 16 found that patients with AA genotype required less postoperative morphine dose than patients with genotype AG or AA. Also, Liu et al, 6 found that patients carrying one or 2 copies of the minor allele (G allele) required significantly more intraoperative remifentanil than in patients without the minor allele ( p =0.001). We performed our study on Jordanian patients (Arab ethnic group) and our findings coincide with Liu et al, 6 where the remifentanil consumed in the intra-operative time to maintain a SBP between 90-100 mm Hg was higher in AG gene compared with AA gene.…”
Section: Discussionmentioning
confidence: 98%
“…Also, Liu et al, 6 found that patients carrying one or 2 copies of the minor allele (G allele) required significantly more intraoperative remifentanil than in patients without the minor allele ( p =0.001). We performed our study on Jordanian patients (Arab ethnic group) and our findings coincide with Liu et al, 6 where the remifentanil consumed in the intra-operative time to maintain a SBP between 90-100 mm Hg was higher in AG gene compared with AA gene. The mean required dose of remifentanil for patients with AG gene was 0.316 µg kg -1 min -1 , and for the patients with AA gene it was 0.173 µg kg -1 min -1 ( p <0.0001).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations